Previous Archaeological Excavations along the 'Ostlänken' Railway Corridor 1965-2012: Ancient monument 78, a grave field (Rogsta, Tystberga parish, Södermanland) - Swedish National Heritage Board (Uppsala University, 2017)
Burial site numbered 78 at Rogsta 1, Tystberga parish, Södermanland was investigated in 1970. The site was initially cleared in 1969. The investigation took place as part of the expansion of the E4 highway. The investigation was carried out during 26/09/1969 to 28/11/1969 and 01/06/1970 to 19/09/1970.

Almost 70 features and a number of graves was discovered during the investigation. 60 of these were visible after clearing and consisted of rather flat, preferably round and irregular stone settings.

Purpose:

The aim of this study was to investigate remains no. 78 at Rogsta 1, Tysberga parish, Södemanland. The investigations were necessary because of the construction of a stretch European Route E4 between Nyköping and Lästringe.

The ZIP-file contains three shapefiles with information on trenches, ancient monuments, archaeological finds and other data from the archaeological survey, as well as one geo-referenced map (© Lantmäteriet i2014/00696) of the survey in GeoTIFF-format.

1970 undersöktes ett gravfält, fornlämning nr. 78 vid Rogsta 1, Tystberga socken, Södermanland. Avtorvning och rensning utfördes hösten 1969. Undersökningen kom till stånd på grund av utbyggnaden av europaväg 4, delen Nyköping-Lästringe. Undersökningen pågick under tiden 26/09/1969 till 28/11/1969 och 01/06/1970 till 19/09/1970.

Vid undersökningen påträffades närmare ett 70-tal anläggningar och ett antal gravar. Ett 60-tal av dessa var synliga efter avtorvning och rensning och utgjordes av tämligen flacka, företrädesvis runda och oregelbundna stensättningar.

Syfte:

Syftet var att undersöka fornlämning nr 78 vid Rogsta 1, Tystberga socken, Södermanland, på grund av utbyggnaden av europaväg 4, delen Nyköping-Lästringe.

ZIP-filen innehåller data i form av tre shapefiler med information om eventuella schakt, påträffade forn- och kulturlämningar och fynd samt andra metadata från den arkeologiska utredningen, samt en georefererad karta (© Lantmäteriet i2014/00696) över utredningsområdet i GeoTIFF-format.
Tidigare arkeologiska undersökningar längs Ostlänken-korridoren 1965-2012: Fornlämning 78, ett gravfält (Rogsta, Tystberga sockenn, Södermanland)
Keywords: finds; fynd; HISTORY; HISTORIA; Archaeology; Arkeologi